2001
DOI: 10.1007/bf02982082
|View full text |Cite
|
Sign up to set email alerts
|

Function and Clinical Significance of Platelet-Derived Microparticles

Abstract: Microparticles released from platelets (PMPs) may play a role in the normal hemostatic response to vascular injury because they demonstrate prothrombinase activity. PMPs were first observed as released vesicles from platelets following adhesion to vessel walls, and flow cytometry is now the most widely used method for studying PMPs. PMPs are thought to play a role in clinical disease because they express phospholipids that function as procoagulants. High shear stress can initiate both platelet aggregation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 111 publications
3
89
0
1
Order By: Relevance
“…PDMP were detected using a modification of the previously reported method. [4][5][6][7] An aliquot (10 ml) of platelet suspension (3 Â 10 8 /ml) was added to 100 ml of 2-[4-(2-hydroxyethyl)-1-piperazinyl] ethanesulphonic acid (HEPES)-Tyrode's buffer containing 5 mmol/l ethylene glycol-bis-(2-aminoethyl ether)-N,N,N 0 ,N 0 -tetraacetic acid (EGTA), and both intact and aggregated platelets were removed by centrifugation at 1000 g for 15 min to obtain a supernatant that only contained microparticles. Then washed intact platelets (10 ml, 3 Â 10 8 /ml) were added to the supernatant, and incubation with KMP-9 (a fluorescein isothiocyanate (FITC)-labelled monoclonal antibody for platelet glycoprotein (GP) IX was performed for 30 min in the dark at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PDMP were detected using a modification of the previously reported method. [4][5][6][7] An aliquot (10 ml) of platelet suspension (3 Â 10 8 /ml) was added to 100 ml of 2-[4-(2-hydroxyethyl)-1-piperazinyl] ethanesulphonic acid (HEPES)-Tyrode's buffer containing 5 mmol/l ethylene glycol-bis-(2-aminoethyl ether)-N,N,N 0 ,N 0 -tetraacetic acid (EGTA), and both intact and aggregated platelets were removed by centrifugation at 1000 g for 15 min to obtain a supernatant that only contained microparticles. Then washed intact platelets (10 ml, 3 Â 10 8 /ml) were added to the supernatant, and incubation with KMP-9 (a fluorescein isothiocyanate (FITC)-labelled monoclonal antibody for platelet glycoprotein (GP) IX was performed for 30 min in the dark at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…3,4 PDMP have procoagulant activity, and some studies have assessed the potential role of PDMP in diabetic complications. [4][5][6][7][8] Monocytes also can synthesize procoagulants, which are largely tissue factors, 9,10 and monocyte vesiculation is a possible mechanism for the dissemination of membrane-associated procoagulant activity. 11 We previously reported that a high level of monocyte-derived microparticles (MDMP) may be a marker of vasculopathy in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Platelet microparticles, released after activation, 29 have procoagulant effects, might promote platelet adhesion to the vessel wall, might promote thrombin generation, and are implicated in many disease processes, including the atherosclerotic complications of diabetes. 30 Although there are few reports of raised platelet microparticles in hypertension, they could play a role in thrombotic complications, being produced when platelets are exposed to increased shear force seen in hypertension.…”
Section: Evidence Of Platelet Activation In Hypertensionmentioning
confidence: 99%
“…Our findings suggest that PDMPs may have a wide range of biological actions, including procoagulant, proinflammatory, and proatherogenic activities 7,37) in healthy individuals. Accumulating evidence indicates that PDMPs enhance the expression of cell adhesion molecules, recruit monocytes on the vascular wall, and induce the proliferation of smooth muscle cells 43,44) , thereby exerting pro-atherogenic activity 7,20,37,45) . The major factor leading to cellular cross-talk may be the ability of PDMPs to convey biological effectors.…”
Section: Discussionmentioning
confidence: 79%
“…P-selectin and CD40 ligand 6,7) . Progressive atherosclerosis induces the elevation of PDMPs via shear-induced platelet activation 8,9) .…”
mentioning
confidence: 99%